(untitled) (Voice: A Biannual & Bilingual Journal, 2024)
Reading comprehension is crucial because it enables students to understand, interpret, and engage with texts, fostering critical thinking and effective communication skills. This study investigates the reading proficiency of Tharu and non-Tharu students within a multilingual educational framework. The data was collected from a sample of 30 grade four students (15 Tharu and 15 non-Tharu) who studied at a community school in Kohalpur Municipality, Banke District during the academic year 2080/81 B.S. The researcher employed stratified simple random sampling method to ensure representativeness. Data collection included reading comprehension tests, vocabulary assessments, and other skill-based tasks aligned with the multilingual education curriculum. Basic statistical tools were used for analysis. The findings indicate marginal differences in overall academic performance between Tharu and non-Tharu students. Tharu students showed strengths in specific skill domains such as comprehension of unseen texts and vocabulary application. Despite this, it underscores the influence of educational backgrounds and cultural factors on academic outcomes. This highlights the need for tailored pedagogical strategies for teaching reading in diverse linguistic contexts.